Pathological Relevance of Anti-Hsp70 IgG Autoantibodies in Epidermolysis Bullosa Acquisita - Tukaj, Stefan; Mantej, Jagoda; Sitko, Krzysztof; Zillikens, Detlef; Ludwig, Ralf J.; Bieber, Katja; Kasperkiewicz, Michael (Frontiers in Immunology, 2022)
Stress-induced heat shock protein 70 (Hsp70) is a key intra- and extracellular molecular chaperone implicated in autoimmune processes. Highly immunogenic extracellular Hsp70 can activate innate and acquired (adaptive) immune responses driving the generation of anti-Hsp70 autoantibodies that are frequently observed in inflammatory/autoimmune disorders. We recently described the direct pathological role of extracellular Hsp70 in epidermolysis bullosa acquisita (EBA), an anti-type VII collagen autoantibody-mediated autoimmune blistering skin disease. Here, we determined the role of anti-Hsp70 autoantibodies in EBA. We observed that circulating anti-Hsp70 IgG autoantibodies were significantly elevated in EBA patients compared to healthy individuals and positively correlated with serum levels of pro-inflammatory interferon gamma (IFN-γ). The pathophysiological relevance of anti-Hsp70 IgG autoantibodies was demonstrated in an antibody transfer-induced EBA mouse model in which elevated serum levels of anti-Hsp70 IgG were found. In addition, anti-Hsp70 IgG-treated animals had a more intense clinical and histological disease activity, as well as upregulated nuclear factor kappa B (NF-κB) activation in skin biopsies compared to isotype-treated animals. Our results suggest that autoantibodies to Hsp70 may contribute to EBA development via enhanced neutrophil infiltration to the skin and activation of the NF-κB signaling pathway in an IFN-γ-associated manner.